Managing quality in architecture : integrating BIM, risk & design process - Nelson, Charles (Charles E.); Nuttall, Gordon (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, an imprint of the Taylor & Francis Group, 2017)
"Completely revised throughout for this second edition, Managing Quality in Architecture addresses the new ISO 9001 standards after the significant 2015 revision. ISO 9001 is the global standard for quality, and firms certified under the 2008 edition have 3 years to upgrade their quality systems to the new Standard. This book helps architects, engineers and other designers working in the built environment to develop appropriate quality systems that meet the requirements of the international Standard. Importantly, the 2015 Standard integrates risk management with quality, something that earlier versions did not. Risk is an extremely important factor in professional design practice, and this important element is fully explored in the new edition. Similarly the role of BIM in quality management is addressed as an integral part of practice. International contributions from the USA and Australia provide expertise in each topic and case studies from the USA, Japan, Australia, New Zealand and the United Nations Office of Project Services provide easy-to-follow illustrations of the important areas to understand. The focus is completely practical, rather than theoretical, affording readers a concise picture of how the issues of excellence and quality performance flow across every aspect of design practice."--Provided by publisher
Chapter 1 Surviving & Thriving in a Swiftly Evolving Professional Environment -- chapter 2 Why Quality? -- chapter 3 Lessons from the Leaders: Case Studies in Quality -- chapter 4 Creating Efficient, Effective Quality Systems -- chapter 5 Harnessing the Power of ISO 9001 -- chapter 6 Vision, Leadership, Planning & Brand -- chapter 7 People -- chapter 8 Integrating BIM, Risk & Design Process -- chapter 9 Business, Connectivity & Marketing -- chapter 10 Project Quality: Techniques that Deliver Results -- chapter 11 Pushing the Envelope: The Future of Practice -- chapter 12 Appendices.
Includes bibliographical references and index.
Keywords: Architectural design -- Risk management; ISO 9000 Series Standards; Total quality management; Building information modeling; Architectural services marketing